The effect of the stakeholders’ pressure on environmental accounting reporting of SMES In Shanxi Province, China - Zhao, Xin (2022)
The small and medium enterprises (SMEs) in China have achieved rapid and sustainable growth for more than three decades that have also contributed to the China's economic development. There are growing concerns on how the human social and economic related activities especially have contributed to the serious damage on the environment which can in turn harmful to the quality life and the future generations. These unwanted impacts are now becoming evident and cause the degradation of environment and scarcity of world natural resources reserve. However, the studies on the public's sensitivity to environmental issues are still scarce which signal for more research to be conducted on the environmental topics. Therefore, the objective of this study is to examine the pressure of stakeholders, namely External stakeholders (Government, Customers, Suppliers, Community, and Media) and Internal stakeholders (Shareholders and Employees) of SMEs in Shan Xi Province in China towards the need to comply with environmental accounting reporting. Five hundred copies of questionnaires were distributed, but only two hundred twelve ready copies were subsequently collected. The data was then analyzed by utilizing Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS 3.3.2. The results of this study indicate that the pressures from Government, Community, Media, Shareholders, and Employees do have an effect on EAR. The pressures from Customers, Suppliers don’t have any effect on EAR. The insights of this study prove that the Government, Community, Media, Shareholders, and Employees in SMEs in Shan Xi Province do concern of the environmental issues due to fact that environmental accounting reporting can improve SME's performances concerning the environment, inventory and controlling costs, efficient technologies with less pollution, non-polluting products.